USE FLOUR PAJURO (ERYTHRINA EDULIS) AS FOOD SUPPLEMENT IN GUINEA PIG – LIMA - Guevara, J. (2013)
The objective of this research was to use effectively pajuro flour (Erythrina edulis) as a food supplement in guinea pigs. Was performed on the premises of guinea pigs shed CAS Agribusiness UNMSM Engineering, located in San Juan de Lurigancho, being treatments: T1. Green alfalfa (10% of live weight) + Concentrate without pajuro flour (Erythrina edulis); T2. Green alfalfa (10% of live weight) + Concentrate + 1.0% pajuro flour (Erythrina edulis); T3. Green alfalfa (10% of live weight) + Concentrate + 2.0% pajuro flour (Erythrina edulis). 27 male guinea pigs weaned Line Peru 21 + 2 days of age were used, from the guinea pig farm Cieneguilla UNALM. Design completely randomized with 3 treatments and 3 replications was used, taking 3 animals per replicate. The animals were randomly distributed, previously identified in 09 cages disinfected. The hand experience lasted 4 weeks. Data were analyzed using the SAS program and the mean difference Duncan test was used. There was significant difference between treatments in feed intake of dry matter, obtaining at the end of the evaluation period, average consumption: 734.0 g (T1), 681.33 g (T2) and 650.43 (T3); with respect to the weight gain was: 456.67 g (T1), 398.33 g (T3) and 392.00 g (T2) g, with significant difference between treatments. Feed conversion exists significant difference between treatments, being higher the T3 and T1 with 1.7, followed by T2 with 2.1. In percentage carcass yield the best results presented guinea pigs with 75.87% of T3, followed by T2 and T1 with 72.44% with 70.39%, showed no statistically significant difference. Regarding the economic merit of beneficiaries cuyes T3 was the best (S /. 7.58), followed by T2 (S /. 6.55) and finally the T1 (S /. 6.49). We conclude that the flour pajuro has positive effect on performance by using it as a food supplement.